Al-Islam dan Kemuhammadiyahan (Aik) dalam Pandangan Mahasiswa Universitas Muhammadiyah Malang (Umm) - Faridi Faridi (STAIFAS-Press, 2021)
There are three reasons for al-Islam and Kemuhammadiyahan (AIK) to be used as courses at Muhammadiyah Higher Education, including: so that students are able to become Indonesians who are Muslim and have a modern mindset; students can be touched by their souls and able to practice their values; and fostering student ethics in the midst of the Muhammadiyah Higher Education environment. However, when AIK came into contact with students who had various religious ideological backgrounds, it gave birth to various perceptions. Based on this reality, the focus of this research is formulated in the form of a question: how are students' responses and perceptions to the AIK course system? This research is descriptive analytical with data collection techniques in the form of interviews and open-ended questionnaires. This research concluded that all respondents agreed that AIK was used as a subject for reasons, among others: it was able to understand Muhammadiyah's struggle; and he is able to have a strong Islamic provision, knowledge and understanding of pure Islam, and can practice Islamic values ​​in real life. However, AIK learning is considered too monotonous which emphasizes cognitive aspects, so that AIK does not encourage the awakening of daily values; learning methods, facilities and infrastructure also need improvement so that students avoid burnout. Keywords: religion, Islam, students Ada tiga alasan al-Islam dan Kemuhammadiyahan (AIK) dijadikan mata kuliah di Perguruan Tinggi Muhammadiyah, antara lain: agar mahasiswa mampu menjadi bangsa Indonesia yang beragama Islam dan mempunyai alam pikiran modern; mahasiswa dapat tersentuh jiwanya serta mampu mengamalkan nilai-nilainya; dan menumbuhkan etika kemahasiswaan di tengah-tengah lingkungan Perguruan Tinggi Muhammadiyah. Namun, ketika AIK bersentuhan dengan mahasiswa yang mempunyai latar ideologi keagamaan yang beragam melahirkan berbagai persepsi. Berdasarkan realitas tersebut, fokus riset ini dirumuskan dalam bentuk pertanyaan: bagaimana respon dan persepsi mahasiswa terhadap sistem mata kuliah AIK?. Riset ini bersifat deskriptif analitis dengan teknik pengumpulan data berupa wawancara dan angket yang sifatnya terbuka. Riset ini menyimpulkan, semua responden menyetujui AIK dijadikan mata kuliah dengan alasan, antara lain: bisa untuk memahami perjuangan Muhammadiyah; dan ia mampu memiliki bekal keislaman yang kuat, pengetahuan dan pemahaman tentang Islam yang murni, serta dapat mengamalkan nilai-nilai Islam dalam kehidupan yang sebenarnya. Namun pembelajaran AIK dinilai terlalu monoton yang menekankan pada aspek kognitif, sehingga AIK kurang mendorong terbangunnya penjiwaan nilai nilai keseharian; metode pembelajaran, sarana maupun prasarana juga perlu pembenahan agar mahasiswa terhindar dari kejenuhan. Kata Kunci: agama, Islam, mahasiswa